2020
DOI: 10.12669/pjms.36.5.2365
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gender equality attitudes of Turkish and Foreign Nursing Students at a Private University

Abstract: Objective: To determine the gender equality attitudes of nursing students studying at a private university, the sociodemographic factors affecting gender equality, and the difference in gender attitudes between Turkish and foreign students. Methods: This cross-sectional study was carried out in the Faculty of Nursing at Near East University in March and April 2019. Three hundred six students studying in Turkish and English nursing programs in the thirdyear of study were included in the research. A sociod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The literature review underscores the intricate relationship between religiosity, gender inequitable attitudes and their societal implications and establishes a strong global correlation between religiosity and gender inequitable attitudes, emphasizing the potential stealth effects of religious impact (see Seguino, 2011; Cos ¸kun and € Ozdilek, 2012). Abendroth et al (2014) and Tekbas and Pola (2020) extend the discussion by highlighting how gender equality, advocating for equal access to resources, opportunities and power, transcends societal aspects into the realm of religion. The intersectionality of gender and religion is deemed crucial, demanding comprehensive strategies that challenge existing practices, norms and policies (Abendroth et al, 2014;Subrahmanian, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature review underscores the intricate relationship between religiosity, gender inequitable attitudes and their societal implications and establishes a strong global correlation between religiosity and gender inequitable attitudes, emphasizing the potential stealth effects of religious impact (see Seguino, 2011; Cos ¸kun and € Ozdilek, 2012). Abendroth et al (2014) and Tekbas and Pola (2020) extend the discussion by highlighting how gender equality, advocating for equal access to resources, opportunities and power, transcends societal aspects into the realm of religion. The intersectionality of gender and religion is deemed crucial, demanding comprehensive strategies that challenge existing practices, norms and policies (Abendroth et al, 2014;Subrahmanian, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Abendroth et al. (2014) and Tekbas and Pola (2020) extend the discussion by highlighting how gender equality, advocating for equal access to resources, opportunities and power, transcends societal aspects into the realm of religion. The intersectionality of gender and religion is deemed crucial, demanding comprehensive strategies that challenge existing practices, norms and policies (Abendroth et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Relevant studies have shown that compared with CT-guided renal biopsy, this method is safe, economical, less traumatic, shorter in recovery period, and has strong operability and reproducibility. [17][18][19] Nursing care for complications. B ultrasoundguided percutaneous renal biopsy is a traumatic examination.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 Relevant studies have shown that compared with CT-guided renal biopsy, this method is safe, economical, less traumatic, shorter in recovery period, and has strong operability and reproducibility. 17 - 19 …”
Section: Discussionmentioning
confidence: 99%